Dampak Bullying Terhadap Kesehatan Mental Anak Sekolah Dasar - Hardiana; Ade Cyntia pritasari (Universitas Negeri Surabaya, 2025)
This research aims to find out how bullying impacts the mental health of children in elementary school. This research uses a descriptive qualitative approach and literature study. The results showed that bullying can have an impact on children's psychological conditions, such as anxiety, depression, insecurity, and decreased self-confidence. At school, these psychological impacts often interfere with children's learning concentration and social interaction. In addition, bullying can also cause physical health problems such as digestive problems, headaches, and sleep problems. In this study, researchers found that high levels of bullying in schools lead to an unsafe environment, which has a negative impact on children's learning spirit and academic development. In conclusion, bullying is one of the main factors that can affect children's psychology. Therefore, this study emphasizes the importance of collaboration between schools, parents, and mental health professionals to create a safe and supportive environment for children's development. Anti-bullying programs and psychological support for victims are important ways to prevent the negative effects of bullying and maintain the mental health of children in primary schools.